Evaluation of Petrophysical Characteristics of Mishrif and Yamama Reservoirs, in Garraf Oil Field, Southern Iraq, Based on Well-Logging Interpretation - Neamah, Ali Kareem; Al-Khafaji, Amer Jassim; Al-Sadooni, Fadhil Nomas (Iraqi Journal of Science, 2022)
The Mishrif and Yamama Formation are the main reservoirs in the Garraf oilfield, Nasiriyah city, of the Euphrates Subzone, Mesopotamian Basin, Southern Iraq. The Garraf oilfield structural pattern corresponds with the similar anticline forming the oilfields of Rafidain and Dujaila and is parallel to the main trend of Zagros, indicating simple coaxial deformation. The petrophysical properties are evaluated using the Interactive Petrophysics V3.5 software. This comprises determining the lithology, mineralogy, and matrix for the investigated reservoirs, as estimating clay volume, total, effective, and secondary porosity, water saturation, permeability, and determining the net pay and gross thickness. The findings of this investigation indicated that the Mishrif formation is divided into two main units separated by a marl layer, with the upper unit having poor reservoir qualities and the lower unit having favorable ones. As a result, there are nine reservoir units in the lower main unit (M1, M1.2, M2, L1, L1.2, L2, L2.2, L2.3, and L2.4). The best and largest reservoir unit capacity is Unit L1.2, with exceptional petrophysical characteristics. Lower units L2.2, L2.3, and L2.4 are nearly saturated in reservoir water, with a little oil in some wells. YA, YB1, and YB2 are the three reservoir units that make up the Yamama formation. Unit YA is the best reservoir unit because of its petro physical properties.